Analysis Of the Framing of News of the 2024 Presidential Candidate in The Period Leading to The Campaign in the 2024 Election on The Media Jawapos.Com and Kompas.Com - MF, Salzafira Al Madinah; Wijayanti , Qoniah Nur (Intitute of Computer Science (IOCS), 2023)
This study analyzes how online media, especially Jawapos.com and Kompas.com, frame news related to the 2024 Presidential election in Indonesia. The study used Robert N. Entman's model framing analysis to identify four framing elements: problem definition, causal diagnosis, moral judgment, and resolution recommendations. The results of the analysis showed that both media highlighted the statements of the leader or candidate, gave positive moral assessments on several aspects, and identified issues that needed to be addressed. However, not all news stories provide information about the cause of the problem or resolution recommendations. The study highlights the important role of online media in shaping people's perceptions of political issues and presidential candidates.